Structural conditions and ethical dilemmas of the integration of Artificial Intelligence in Latin American Public Higher Education - Paola Elizabeth Cortez Clavijo; Marjorie Alexandra Coronel Suárez; Lourdes Hilda Ortega Maldonado; Félix Javier Rosales Borbor; Cynthia Nataly Espíndola Vásquez; María Magdalena Gonzabay Espinoza; Mónica Karina Jaramillo Infante; Xavier Eduardo Espíndola Vásquez (Neutrosophic Sets and Systems)
This study, using a neutrosophic approach, evaluates the integration of artificial intelligence in Latin American public higher education, focusing on the perceptions and ethical dilemmas of university stakeholders. Two groups of students in a scientific writing course were compared: one that used AI tools during the writing process and another that employed traditional methods. The results show that the use of AI favors active participation and the final quality of the essays, although it does not significantly impact prior knowledge or argumentative depth. The intervention reveals both benefits, such as greater engagement and improved performance, and ethical tensions related to privacy, equity, and transparency. The analysis highlights that the adoption of AI in educational contexts requires policies and practices that promote inclusion, ethics, and social justice. The results suggest that the integration of AI can enhance educational quality and participation, but always within a framework of critical reflection that ensures respect for ethical principles and equity in Latin American universities.